Determination of orthometric elevations using gnss-derived height with the egm2008 geoid height model - Menegbo, Emmanuel (International Journal of Advanced Geosciences, 2017)
The Global navigation satellite systems (GNSS) has imparted positively on civilian positioning & surveying in the horizontal component in Nigeria for the past two decades. The GNSS receivers’ data are longitude, latitude & elevation. However, the vertical distance measurement have not been fully exploited by geodetic and land surveyors. The GNSS derived heights are ellipsoidal elevation. To convert the GNSS elevation to orthometric heights, a geoidal elevation models is needed. The Earth Gravitational Model, 2008 (EGM2008) is a global geoidal models that can be used to obtain GNSS orthometric heights by defining the relationship with the ellipsoid. This work determines GNSS-derived orthometric heights with ellipsoid-geoidal relationship using GPS ellipsoidal heights and EGM2008 geoidal model GIS data. The EGM2008 GIS data was downloaded and interpolated with GPS data to obtain geoidal heights using ArcGIS 10.1. GNSS-derived heights determined with geoid-ellipsoid relationship formula. The result shows minimum elevation of -2.37599m and maximum elevation of 53.8566m.The derived orthometric heights use to create a model in raster format. The orthometric elevation models created useful in all vertical surveying work, construction work and urban planning. The GNSS orthometric heights models need to be compare with spirit levelling and the local geoidal model determined for improve accuracy.